Performance Description of Untung Suropati Green Terminal in Pasuruan - Sedayu, Agung; Pamungkas, Sigit Adi (Proceedings of the International Conference on Green Technology, 2017)
Untung Suropati Terminal is a road transport passenger terminal with Type B in Pasuruan City that serves public transportation between cities in the province of East Java. At this time the Untung Suropati terminal is quiet from visitors and public transport vehicles. The condition of the physical building is mostly damaged. This study aims to perform user voice description of the performance of Untung Suropati terminal. The description describes the level of user satisfaction. Description refers to the principles of green terminal using statistical descriptions method. The results achieve 12 performance variables are Security (X1), Safety and Health (X2), Responsibility (X3), Building Utility (X4), Architectural Esthetics (X5), Ease and Affordability (X6), Reliability Transportation (X7), Building Durability (X8), Frequency and Density (X9), Comfort and Regularity (X10), Availability and Capacity of Public Facilities (X11), and Implementation of Environmentall-Friendly Concepts (X12). The satisfactory scale (scale 4) was obtained for 11 performance variables and only 1 variable gets scores on a very satisfactory scale (scale 5) that the variable of Ease and Affordability (X6).